Health Disparities Between Diabetic Patients Under Private and Public Health Coverage in Puerto Rico, 2000 - Pérez-Perdomo, Rosa; Pérez-Perdomo, Cynthia M.; Disdier-Flores, Orville M. (Puerto Rico Health Sciences Journal, 2011)
see manuscript